(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2017)
This is a book about social movements. Unlike most such books, it seeks to understand the phenomenon of social movements with a view to assist them (us) in discerning a way forward in the current political context of neoliberalism. The authors, who are both movement activists and academics, argue that neoliberalism is mortally wounded and seemingly unable to reinvent capitalism. This presents an opportunity for social movements. What they provide is not a blueprint or road map but rather a tool kit - a set of analytical resources which movement activists can use collectively to consider how to act, and which strategies might help to deliver another world.